An interactive website for informed contraception choice: randomised evaluation of Contraception Choices. (June 2020) - Stephenson, Judith; Bailey, Julia V; Gubijev, Ana; D'Souza, Preethy; Oliver, Sandy; Blandford, Ann; Hunter, Rachael; Shawe, Jill; Rait, Greta; Brima, Nataliya; Copas, Andrew
Objective: Improving use of effective contraception to prevent unintended pregnancy is a global priority, but misperceptions and concerns about contraception are common. Our objective was to evaluate an interactive website to aid informed choice of contraception. Methods: The Contraception Choices website is an interactive digital intervention which offers tailored advice to aid contraception decision-making (www.contraceptionchoices.org ). In a parallel single-blind trial, we randomised 927 women aged 15–30 years from six clinic settings to access the intervention website (n = 464) or to a waiting-list control group (n = 463). The study was initially a feasibility trial, evolving into an evaluation of efficacy, with two primary outcomes at six months: long-acting reversible contraception (LARC) use, and satisfaction with contraceptive method. Secondary outcomes included self-reported pregnancy and sexually transmitted infection diagnoses. Free-text comments on the 3 and 6 month outcome surveys were analysed thematically. Findings: There was no significant difference between intervention and control groups in the proportion of women using LARC [30.4% intervention versus 31.0% control; adjusted odds ratio 0.87 (95% confidence interval 0.60 to 1.28)]; satisfaction with contraceptive method [82.6% versus 82.1%; adjusted ordinal odds ratio 0.93 (95% CI 0.69 to 1.25)]; self-reported pregnancy [3.3% versus 4.1%; adjusted odds ratio 0.90 (95% CI 0.45 to 1.79)] nor sexually transmitted infection [5.3% versus 4.7%; adjusted odds ratio 0.72 (95% CI 0.55 to 2.36)]. Highly positive free-text comments from intervention participants indicated that the website facilitates contraception choice and can help women feel better prepared before consultation with healthcare providers. Interpretation: The Contraception Choices website was popular for its design, trustworthy information and decision aids but it was not associated with significant differences in use of LARC or satisfaction with contraceptive method. An interactive website can aid contraception choice, but interventions that address factors beyond women's control, such as access to services, and partner, family or community influences are needed to complement this approach. Research in context: Preventing unintended pregnancy through effective use of contraception is essential for women's health, but choosing between different contraceptive methods can be challenging, and the opportunity for adequate discussion during routine consultations is often constrained. Evidence before this study: We conducted two systematic literature reviews: 1) Factors influencing contraception choice, uptake and use: a meta-synthesis of systematic reviews; and 2) Effectiveness of interactive digital interventions (IDI) for contraception choice, uptake and use. For the first review we searched PubMed, CDSR, Epistemonikos, DoPHER, DARE, NHS Economic Evaluation Database, Campbell Library, NIHR Health Technology Assessment, and Health Evidence Canada databases for systematic reviews which addressed contraceptive choice, uptake or use, from 2000 to 2017. PROSPERO registration number: CRD42017081521https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=81521 . We synthesised the findings of 18 systematic reviews of mostly moderate or high quality. They highlighted the importance of women's knowledge, beliefs, perceptions of side effects and health risks, as well as relationship status, social network, economic and healthcare factors on contraception choice and use. For the second review, we searched 23 electronic databases, trials registers and reference lists for randomised controlled trials of IDI for contraception, including CENTRAL, MEDLINE, EMBASE, CINAHL, ERIC, ASSIA and PsycINFO, from start date to June 2017. PROSPERO registration number: CRD42017081636. We found only five randomised trials of IDI, all from the USA. Risk of bias prevented synthesis of results.www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=81636 . Added value of this study: Women's common concerns about contraception – fear of hormones, weight gain, cancer, infertility, mood changes, breaks from contraception and changes in bleeding patterns – underpinned development of a new interactive website (www.contraceptionchoices.org ). Contraception Choices addresses women's concerns through succinct text; Q and A format ( Frequently Asked Questions, Did you Know? ; videos of women and health professionals); an effectiveness infographic, and an interactive decision aid ( What's right for me? ). In an online randomised trial with 927 women attending clinics, we found no association of the Contraception Choices intervention with the primary outcomes – satisfaction with contraceptive method and uptake of long-acting reversible methods at 6 months. Nor did we find an association with secondary adverse outcomes – sexually transmitted infections or pregnancy. Comments from women indicated that the website can meet young women's need for information on the benefits and drawbacks of contraception, help them to make informed decisions, and feel better prepared before healthcare consultations. Contraception Choices is now available on the NHS website:www.nhs.uk/conditions/contraception/which-method-suits-me Implications of all the available evidence: Interactive digital interventions (websites) can aid contraception choice, but other intervention research is needed to address wider influences on unintended pregnancy, including partner views, friends, family, the media, wider society and experiences with healthcare professionals. Future research could examine the impact of the website in different settings, e.g. schools or different countries. We hypothesise that use of the website during contraceptive consultations might improve the efficiency or quality of consultation, for both patients and healthcare providers. Appropriate methodology and time-scale for evaluating digital health interventions remains a key question.